Enhancing the use of crop genetic diversity to manage abiotic stress in agricultural production systems, 23-27 May 2005, Budapest, Hungary - Jarvis, D.; Már, I.; Sears, L. (2006)
Diversity can provide one means of sustaining and improving the livelihoods of farmers where or when environmental conditions are unfavourable in production systems. Much of the world's agricultural biodiversity is found in environments marginal for agricultural production. It is in such environments where management of high levels of diversity can become a central part of the livelihood management strategies of farmers and the survival of their communities. Loss of such diversity or genetic choices diminishes farmers' capacities to cope with extreme temperatures, drought and salinity. Farmers in stress-prone areas have to take particular care not to introduce non-adapted material which often fails and can lead to erosion of the desired characteristics in local varieties through unwanted crossing. Thus, in the face of constant vulnerability to loss of key stress-resistant types, the management of appropriate diversity of a specific crop constitutes a significant component of livelihood strategies of farmers in highly stressed production environments. Within the global project, 'Strengthening the Scientific Basis of In Situ Conservation of Agricultural Biodiversity On-farm', and other projects concerned with the conservation and use of local crop diversity on-farm, national and international partners have developed tools to measure the amount and distribution of crop genetic diversity on-farm, to analyze the processes that maintain this diversity and to calculate values of this diversity to farmers and other stakeholders. Yet, there are still important unknowns concerning the diversity in local varieties managed by farmers subject to significant abiotic stress. These include: • Whether within farmers' use of diversity for managing abiotic stress: Does the use of stress-tolerant germplasm 'cost' lower yield? In the stressed environment? In benign environments? In both? • How different are the local crop varieties - phenotypically and genetically - with respect to resistance to the specific traits conferring stress tolerance or resistance?• Do the tolerant or resistant populations have sufficient diversity with respect to other characteristics, thus helping farmers to exploit their potential to develop material with further desirable characteristics such as pest resistance, nutritional aspects, grain quality? • Do farmers manage such materials in a specific way to prevent dilution of their stress-resistance characteristics, and does this limit adaptability? From 23 to 27 May 2005, a workshop was held in Budapest, Hungary to refine these questions and to define areas where more basic research that uses tools which assess diversity, its structure and changes would be needed. During the workshop, the participants from Burkina Faso, Morocco, Zimbabwe, Mali, Peru, Vietnam, Tunisia, Hungary, Bolivia, Nepal, Australia, Italy and the US presented their ideas and information from their own work on enhancing the use of crop genetic diversity to manage abiotic stress. The following papers in this proceedings document the partners' presentations and the output of the discussion groups.